(untitled) (The South East European Journal of Economics and Business, 2025)
The study examines the relation between credit risk and monetary policy in Albania’s banking sector from 2015 to 2023, utilizing the Autoregressive Distributed Lag (ARDL) model. It analyzes post-crisis developments, particularly the Central Bank’s (CB) stabilization efforts and the write-off of NPLs. The findings show that higher CB rates increase NPLs in the short and long term. Following the 2008 financial crisis and the COVID pandemic, measures such as NPL write-offs and loan repayment postponements helped mitigate credit risk. Inflation contributed to credit stability by easing debt repayment burdens. Inflation and higher rates ease debt repayment and enhance credit stability. The Loan/Deposit Ratio influences NPLs, as managed decreases in LDR lower credit risk. Additionally, increased CB rates reduce new loan issuance, deterring high-risk borrowers and curbing NPL growth. The study highlights the effectiveness of Albania’s monetary policy in maintaining banking sector stability and supporting economic recovery.